2005
DOI: 10.1038/nature04301
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptors are expressed in developing oligodendrocyte processes and mediate injury

Abstract: Injury to oligodendrocyte processes, the structures responsible for myelination, is implicated in many forms of brain disorder. Here we show NMDA (N-methyl-D-aspartate) receptor subunit expression on oligodendrocyte processes, and the presence of NMDA receptor subunit messenger RNA in isolated white matter. NR1, NR2A, NR2B, NR2C, NR2D and NR3A subunits showed clustered expression in cell processes, but NR3B was absent. During modelled ischaemia, NMDA receptor activation resulted in rapid Ca2+-dependent detachm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
527
3
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 495 publications
(555 citation statements)
references
References 27 publications
23
527
3
2
Order By: Relevance
“…Expression of AMPA/kainate receptors is particularly marked in immature cells of the oligodendrocyte lineage (Itoh et al, 2002), which in the neonatal optic nerve are in the process of forming an exquisitely close morphological arrangement with neighbouring axons (Butt and Ransom, 1993). We and others have recently demonstrated the presence of functional NMDA-type glutamate receptors in oligodendrocyte processes (Salter and Fern, 2005;Káradóttir et al, 2005;Micu et al, 2006)). The activation of these receptors is likely to be important in a variety of diseases and must have significant developmental consequences.…”
Section: Discussionmentioning
confidence: 95%
“…Expression of AMPA/kainate receptors is particularly marked in immature cells of the oligodendrocyte lineage (Itoh et al, 2002), which in the neonatal optic nerve are in the process of forming an exquisitely close morphological arrangement with neighbouring axons (Butt and Ransom, 1993). We and others have recently demonstrated the presence of functional NMDA-type glutamate receptors in oligodendrocyte processes (Salter and Fern, 2005;Káradóttir et al, 2005;Micu et al, 2006)). The activation of these receptors is likely to be important in a variety of diseases and must have significant developmental consequences.…”
Section: Discussionmentioning
confidence: 95%
“…Although, there are evidences for the expression of NMDA receptors on oligodendrocyte processes in white matter [19], oligodendrocytes in retro-orbital optic nerve axons remained normal. But astrocytes underwent reactive changes with the development of extensive filament-rich processes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed perisynaptic localisation of N-methyl-D-aspartate (NMDA) receptors in RGCs [17]. Although there is evidence for the presence of non-NMDA glutaminergic receptors for alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and kainite in the postsynaptic myelinated axons in the central neurons [18] and the expression of NMDA receptors on oligodendrocyte processes in white matter [19], there is no direct evidence of presence of functional NMDA receptors on axons [20]. Therefore, retro-orbital optic nerve axonal degeneration observed in NMDA-induced retinal insult is logically a consequence of primary damage to RGCs; however, damage to intraorbital axons can also be considered a primary site of insult, if future studies provide direct evidence for the presence of functional NMDA receptors over axons.…”
Section: Introductionmentioning
confidence: 99%
“…Oligodendrocytes, expressing AMPA/kainate and N-methyl-D-aspartatereceptors, are also sensitive to glutamate toxicity, which is associated with caspase-3 activation, DNA fragmentation, apoptotic cell death, and demyelination (Domercq et al, 2005;Karadottir and Attwell, 2007;Salter and Fern, 2005;Xu et al, 2008). Damage of the myelin sheath itself may contribute to axonal degeneration by reducing trophic support to axons and impairing axonal transport (Nave, 2010).…”
Section: Possible Consequences Of An Impaired Phosphocreatine Metabolismmentioning
confidence: 99%